An advanced technique to predict time-dependent corrosion damage of onshore, offshore, nearshore and ship structures: Part II = Application to the ship's ballast tank - Kim, D.K. (Society of Naval Architects of Korea, 2020)
In this study (Part II), the empirical formulation of corrosion model of a ship's ballast tank was developed to predict nonlinear time-dependent corrosion wastage based on the advanced data processing technique proposed by Part I. The detail on how to propose generalised mathematical formulation of corrosion model was precisely documented in the previous paper (Part I). The statistical scatter of corrosion data at any exposure time was investigated by the refined method and formulated based on a 2-parameter Weibull distribution which selected the best fit PDF. Throughout the nine (9) steps, empirical formulation of the ship's seawater ballast tank was successfully proposed and four (4) key step results were also obtained. The proposed method in Part I was verified and confirmed by this application of seawater ballast tank, thus making it possible to predict accurate behaviours of nonlinear time-dependent corrosion. Developed procedures and obtained corrosion damage model for ship's seawater ballast tank can be used for development of engineering software. Â© 2020 Society of Naval Architects of Korea